The genome sequence of the Brown-spot Pinion, Agrochola litura (Linnaeus, 1761) [version 1; peer review: 2 approved] - David C. Lees (Wellcome Open Research, 2023)
We present a genome assembly from an individual female Agrochola litura (the Brown-spot Pinion; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 772.2 megabases in span. Most of the assembly is scaffolded into 32 chromosomal pseudomolecules, including the W and Z sex chromosomes. The mitochondrial genome has also been assembled and is 15.55 kilobases in length. Gene annotation of this assembly on Ensembl identified 19,500 protein coding genes.